Theological and Secular Meta-Narratives of Politics: Anabaptist Origins Revisited (Again) - Heilke, Thomas W. (Modern theology, 1997)
Until recently, scholars both friendly and hostile to Anabaptism have agreed that its origins and development to the present time could be rendered in a coherent, continuous narrative, making Anabaptist identity relatively unproblematic. This consensus has broken down. The present essay seeks to show how newer, ostensibly "objective" social-science accounts of Anabaptism in fact offer a secular counter-narrative to the Anabaptists’ accounts of their own activity. This seemingly confined dispute over Anabaptist origins and identity leads to a wider consideration of the significance of both Christian and social-scientific uses of meta-narratives or "narrative bases" in political and ethical reflection.